2009
DOI: 10.1080/01140670909510259
|View full text |Cite
|
Sign up to set email alerts
|

Yield‐density relationship for potato (Solarium tuberosum) and common bean (Phaseolus vulgaris) in intercropping

Abstract: Methodologies of competitive interaction quantification between crops are not widely investigated. Therefore, field experiments (using addition series) were conducted in 2005 and 2006, to quantify interspecific and intraspecific competition coefficients and, also, the relative competitive ability (RC) of potato (Solanum tuberosum) and common bean (Phaseolus vulgaris). The relations between potato tuber yield/plant and common bean density at various densities of potato and also with potato density at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Direct drill planting and mechanized harvesting has enabled farmers to gain higher yield of rapeseed from attaining higher plant densities (Hu et al, 2016 ). Although previous studies reported that after a saturation threshold, yield per unit area does not increase with plant density because of high intra specific competition for resources (Raey and Ghassemi-Golezani, 2009 ). Al-Barzinjy et al ( 1999 ) showed that dry biomass per plant, seed weight per plant and number of pods per plant decrease with increasing plant density, whereas seed yield m −2 peaks at 50 plants m −2 and decreases at higher densities, following a parabolic curve relationship.…”
Section: Introductionmentioning
confidence: 92%
“…Direct drill planting and mechanized harvesting has enabled farmers to gain higher yield of rapeseed from attaining higher plant densities (Hu et al, 2016 ). Although previous studies reported that after a saturation threshold, yield per unit area does not increase with plant density because of high intra specific competition for resources (Raey and Ghassemi-Golezani, 2009 ). Al-Barzinjy et al ( 1999 ) showed that dry biomass per plant, seed weight per plant and number of pods per plant decrease with increasing plant density, whereas seed yield m −2 peaks at 50 plants m −2 and decreases at higher densities, following a parabolic curve relationship.…”
Section: Introductionmentioning
confidence: 92%
“…Light is a key environmental factor and an important consideration for agroforestry production [10,11]. Under high planting density, plants increase light capture by expanding their canopy to elevate yield [12]. Studies have also shown that with increasing density, light transmittance to each layer decreases significantly, ultimately affecting yield [13].…”
Section: Introductionmentioning
confidence: 99%
“…Plant density affects yield and the extent of lodging by altering the crop canopy 12 . High plant densities enhance light capture by the canopy and increase yield up to a certain saturation threshold 13 . At high plant densities, the canopy is uniform, stems are thinner, branches are shorter, and maturation is more synchronized, all of which are factors that facilitate mechanized harvesting and decrease yield losses 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%